(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Fibrinolytic enzymes derived from bacteria can be effective as a potent, safe and cost-effective thrombolytic agent for the prevention and treatment of cardiovascular diseases. In this study, microorganisms were isolated from various soil samples and screened for their protease activity and protein concentration. Isolates with higher protease activity were subsequently tested for their thrombolytic and fibrinolytic activity. Of a total 37 isolates, 7 exhibited significant zone in SMA media (zone ratio above 1.3). Of these, 8 isolates showed increased protease activity with values ranging from 120 to 199 U/ml. The highest protease activity was observed for the isolate GST12 obtained from mung bean (green gram) soil. The freeze-dried concentrated crude enzymes were screened by in vitro clot lysis method. Six of these eight concentrated enzymes demonstrated clot lysis above 20%, whereas, enzymes from GST12 and GST21 exhibited the highest clot lysis activity (about 27%), which is comparable with standard drug streptokinase. These two enzymes are also strongly associated with fibrinolytic activity. Our findings identify 8 isolates having potential thrombolytic and fibrinolytic activities that belong to Gram-positive Bacillus. Dhaka Univ. J. Pharm. Sci. 22(2): 125-135, 2023 (December)